64.1k views
2 votes
Choose the expression that is equivalent to the one shown

Choose the expression that is equivalent to the one shown-example-1
User Erico
by
5.0k points

1 Answer

3 votes

(8^(12))/(4^3)

1. Rewrite the expression to get the numerator and denominator with the same base:


((2^3)^(12))/((2^2)^3)=(2^(36))/(2^6)

2. Divide by leavinfg the same base and subtracting the exponents:


(2^(36))/(2^6)=2^(36-6)=2^(30)

Write the result with base 4:


2^(30)=(2^2)^(30/2)=4^(15)As you can see above any of the given expression is equivalent to the given expression.Answer: none of these
User Mgronber
by
5.5k points